An ultra-wideband thin metamaterial linear cross-polarization conversion - Pegah Nochian; Zahra Atlasbaf (Scientific Reports)
Abstract This article presents the design of a novel ultra-wideband, thin metamaterial linear cross-polarization converter (CPC) operating at microwave frequencies. The CPC consists of two concentric deformed rings on a dielectric substrate backed by a metallic surface. It demonstrates co-polarization and cross-polarization reflection coefficients below − 11 and above − 1.1 dB, respectively, over a wide frequency range of 8.75–17.75 GHz, achieving a 68% bandwidth. Within this range, the polarization conversion ratio exceeds 90%, with three prominent peaks at 9.3 GHz, 13 GHz, and 17.4 GHz, reaching 99.5%, 99.8%, and 99.3% respectively. The unit cell dimensions are compact at 6.3 × 6.3 × 2 mm3. The CPC’s performance was analyzed under varying polarization and oblique incidence angles, and the surface current distributions were studied to elucidate the polarization conversion mechanism. Simulations using CST and FEKO demonstrated substantial agreement, also equivalent circuit is determined and compared to CST software. The compact, thin, and ultra-wideband design makes this CPC a promising candidate for applications in advanced communication systems such as radar cross-section reduction and electromagnetic interference suppression. The results are validated further by experimental measurements of the fabricated CPC.